2023
DOI: 10.1038/s41598-023-28402-9
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a new sulfadimidine Schiff base and their nano complexes as potential anti-COVID-19 and anti-cancer activity

Abstract: The primary objective of this study was to describe the cytotoxicity on HEPG-2 cells and to study the COVID‑19 activities of the novel H2L ligand and its Cr and Cu nano-complexes. As well as exploring the chemistry of the prepared nano-complexes. In this paper novel Schiff base, N-(4, 6-dimethyl pyrimidin-2-yl)-4-(((2-hydroxyl naphthalene-1-y l) methylene) amino) benzene—sulfonamidesulfonyl) amide has been synthesized. The novel Schiff base H2L is used to synthesize novel nano and micro-complexes with CrCl2.6H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The signal at δ: 7.50 ppm for NH 2 proton. In addition, the presence of morpholine and aromatic system at δ: 3.30 and 6.90 ppm 25 , respectively, indicates the purity of the prepared ligand (Fig. S1 ).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The signal at δ: 7.50 ppm for NH 2 proton. In addition, the presence of morpholine and aromatic system at δ: 3.30 and 6.90 ppm 25 , respectively, indicates the purity of the prepared ligand (Fig. S1 ).…”
Section: Resultsmentioning
confidence: 98%
“…The 1 H NMR of MBT in DMSO-d6 revealed the appearance of azomethine proton at δ: 7.70 ppm 24 . The NH proton signal was observed at δ: 8.10 ppm 25 . The signal at δ: 7.50 ppm for NH 2 proton.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of ( E )- N -(( E )-3-phenylallylidene)aniline Schiff bases was carried out following modified procedures described in the literature [ 60 , 61 ]. In a nutshell, cinnamaldehyde (0.5 g, 3.85 mmol, 1eq) was dissolved in 10 mL of methanol and reacted individually with the corresponding solutions of aniline derivatives (3.85 mmol, 1eq) in 10 mL of methanol.…”
Section: Methodsmentioning
confidence: 99%
“…The results revealed that the nano-complexes exhibit a greater ability to bind DNA due to their small particle size, which can also be used extensively in economic anticancer studies by the scientists (Figure 25). 36 Topala and co-workers prepared a Schiff base ligand namely N-(2-(pyridine-2-yl)ethyl)quinolone-8sulphonamide by the condensation of solid quinolone-8sulphonyl chloride with 2-(pyridine-2-yl)ethanamine at 0 • C for 1 h, followed by 2.5 h at room temperature and 2 h in an ice bath. Then the metal complexes were synthesized by refluxing the methanolic solution of metal salts (Co, Cu, Ni and Zn) with the Schiff base ligand at room temperature The in vitro antimicrobial potential was screened against P. aeruginosa, E. coli, S. aureus and C. albicans using well diffusion method and the results revealed that the Cu(II) and Ni(II) complexes exhibited greater antimicrobial potential against the respective microorganisms (Figure 29).…”
Section: Introductionmentioning
confidence: 99%